Leo Strauss on Nietzsche's Thrasymachean-Dionysian Socrates: philosophy, politics, science, and religion in the modern age - Torres, Angel Jaramillo (New directions in the humanities, 2018)
Leo Strauss's philosophical Bewegung in light of NietzscheThe will to power and the philosopher of the futurePhilosophy and the natural right of the eternal return of the sameThe anti-theological religion of the eternal return